2007
DOI: 10.1007/s00125-006-0548-1
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral overproduction of interleukin-1 receptor antagonist increases beta cell replication and mass in syngeneically transplanted islets, and improves metabolic outcome

Abstract: Aims/hypothesis Interleukin-1 receptor antagonist (IL1RN, also known as IL1RA) is a naturally occurring inhibitor of IL-1 action and its overproduction protects pancreatic islets from the deleterious effects of IL-1β on beta cell replication, apoptosis and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…IL-1␤ has been shown to break tolerance (30) and facilitate islet antigen presentation (6). In other studies, IL-1Ra inhibited mouse islet allograft rejection (15), increased islet beta cell function during transplantation (31), and improved disease parameters in patients with type 2 diabetes (32). AAT was shown to induce IL-1Ra in human PBMCs (33).…”
Section: Discussionmentioning
confidence: 97%
“…IL-1␤ has been shown to break tolerance (30) and facilitate islet antigen presentation (6). In other studies, IL-1Ra inhibited mouse islet allograft rejection (15), increased islet beta cell function during transplantation (31), and improved disease parameters in patients with type 2 diabetes (32). AAT was shown to induce IL-1Ra in human PBMCs (33).…”
Section: Discussionmentioning
confidence: 97%
“…That hyperglycaemia itself can decrease insulin secretion has led to the concept of glucose toxicity, which implies the development of irreversible damage to cellular components of the insulin production pathway over time [24,25]. The effects of the pro-inflammatory cytokine IL-1␤ have been conclusively shown to impair glucose-stimulated insulin production in mouse, rat and human islets, and to increase ␤-cell death [19,20,26]. In this study, we found that MafA-overexpressing PDMSCs are more resistant to hyperglycaemia-induced or hyperglycaemia and oxidative stress-induced toxicity and damage compared to PDMSCs with the vector control ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This selectivity is further supported by studies showing that maturation of the β cell makes it prone to the toxic effects of IL-1β (118). On the basis of animal studies, IL-1β plays an important role in destruction of transplanted islet grafts (119)(120)(121)(122)(123), and blocking cytokines in clinical islet transplantation has also been suggested as a future intervention to prevent graft destruction (124).…”
Section: β-Cell Destruction and Hdacimentioning
confidence: 92%